Smart Drug Delivery Systems: A New Era in Targeted Therapy (Asian Journal of Pharmaceutics (AJP), 2025)
The world of drug delivery is undergoing a profound transformation. Nowadays, conventional drug deliverysystems (DDS) are not mostly used due to their side effects and limited benefits. We have already entered theera of smart DDS (SDDS) which is an innovative wave of therapy that delivers medications precisely where andwhen required and always in right amounts. The heart of these systems is nanocarriers. These are microscopictransporters engineered to protect and deliver drugs with pinpoint accuracy. These tiny vehicles come in variousforms such as liposomes, nanoparticles, quantum dots, dendrimers, carbon nanotubes, and superparamagneticiron-oxide nanoparticles each offering unique advantages. This controlled delivery shines especially in areassuch as cancer and gene therapy, where precision can make the difference between success and setbacks. Thisreview focuses on the design and preparation of the nanocarriers and explore their real-world applications, fromtargeted tumor treatment to customized gene delivery. It helps in overcoming long-standing limitations posedby conventional drug delivery, SDDS are paving the way for treatments that are not just more effective, but alsosafer and more personalized. This article also gives information regarding the available marketed products of thenanocarriers along with their manufacturer’s details and also the brand names. With smarter, more responsivesystems, the future of disease management looks brighter than ever; bringing us closer to therapies tailored toeach individual’s unique needs